Isolation and characterization of partial insulin-like androgenic gland hormone gene from distal terminal ampoules of three marine shrimp Penaeus species from the Eastern Pacific - Sancho Blanco, Carolina (2018)
The expansion of the shrimp industry depends on scientific advances related to the understanding of reproductive endocrinology that allows the development of aquaculture programs based on biotechnology. An insulin like-androgenic gland hormone (IAG) is synthesized in the male-specific androgenic gland (AG) and it is responsible for sex differentiation in crustaceans. In this study, RNA was extracted from different tissues; amplified cDNA was obtained by reverse transcription-PCR. Nucleotide sequences were analyzed following a bioinformatic approach of the encoding insulin-like androgenic gland hormone gene. This contribution presents the isolation of the partial cDNA encoding IAG from Penaeus vannamei (Lv-IAG), Penaeus occidentalis (Lo-IAG) and Penaeus stylirostris (Ls-IAG) from the distal region of terminal ampoules. In addition, the molecular characterization of these sequences is provided and the resulting aminoacid sequences were used to establish the taxonomic positioning of the IAG gene among other Decapoda species. The isolation of these partial sequences provides evidence about the anatomical location of the AG in Penaeus and is the basis for further characterize the complete cDNA of the AG-specific insulin-like encoding transcript for all species of the genus Penaeus from the Pacific coast of America.